2015
DOI: 10.1088/0957-4484/26/6/065602
|View full text |Cite
|
Sign up to set email alerts
|

Production of three-dimensional quantum dot lattice of Ge/Si core–shell quantum dots and Si/Ge layers in an alumina glass matrix

Abstract: Abstract. We report on the formation of Ge/Si quantum dots with core/shell structure that are arranged in a three-dimensional body centered tetragonal quantum dot lattice in an amorphous alumina matrix. The material is prepared by magnetron sputtering deposition of Al 2 O 3 /Ge/Si multilayer. The inversion of Ge and Si in the deposition sequence results in the formation of thin Si/Ge layers instead of the dots. Both materials show an atomically sharp interface between the Ge and Si parts of the dots and layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 27 publications
1
37
0
3
Order By: Relevance
“…The very recent calculations show that the effective band-gap and exciton binding energy are strongly dependent on the size of the core and shell [12,13]. Our recent studies demonstrated the possibility to produce Ge/Si core/shell QDs [14]. It is also shown that these materials indeed have specific absorption properties that significantly differ from the absorption of either Ge or Si QDs.…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…The very recent calculations show that the effective band-gap and exciton binding energy are strongly dependent on the size of the core and shell [12,13]. Our recent studies demonstrated the possibility to produce Ge/Si core/shell QDs [14]. It is also shown that these materials indeed have specific absorption properties that significantly differ from the absorption of either Ge or Si QDs.…”
Section: Introductionmentioning
confidence: 60%
“…Finally, Ge/Si core/shell materials are more stable at higher temperatures. Ge QDs in alumina disintegrate at temperatures above 700°C, whereas in the core/shell system this limit is shifted to values above 800°C [14]. Optical properties, especially absorption, are important for potential solar cell materials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations